Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PDAM Tirta Pakuan Kota Bogor - Retna, Dewi Wulan; Sulistiono, Angga (Jurnal Ilmiah Manajemen Kesatuan, 2014)
In the free trading era, many companies are met with increasing consumer demands. Companies must provide service excellenæ to satisfr customets. The serviæ quality has a closed relationship with the customer satisfaction. PDAM Tirta Pakuan Kota Bogor, as a public service company, develops the products and services quality. The companies' strategies are providing a goodfoundation for business continuity, encourage the creation ofcustomer satisfaction, establish recommendations through word of mouth. The purpose of this study is to examine the effect of product quality and service quality on customer satisfaction. The results showed that the regression equation ofproduct quality and service quality on customer satisfaction is: Y = 7.054 + 0.164 XI + 0.468 X2. It means that all the independent variables has a positive effect on customer satisfaction. The hypothesis test ofpartial variable product quality and service quality showed significantly, because all the significant value under 0.05. Product quality has significantly positive effect on customer satisfaction. The result ofsimultaneous hypothesis testing are rejecting HO and accepting HI. So it can be concluded that the product quality (XI) and service quality (X2) simultaneously influenæ the customer satisfaction variable. Based on the result study, The Product Quality and Service Quality are the important components to be increased by PDAM Tirta Pakuan Kota Bogor. Keywords: quality products, quality service, customer satisfaction